Pengaruh Strategi Bersaing dan E-Commerce Terhadap Keberhasilan Usaha - Aldino, Alfin; Aramita, Finta (Universitas Medan Area, 2024)
The aim of this research is to analyze and test the influence of competitive strategies and e-commerce on the success of culinary Micro, Small and Medium Enterprises (MSMEs) in Medan Selayang District. This type of research is quantitative with an associative approach. The population is culinary MSMEs located and recorded in the Medan Selayang District area in 2022-2023 as many as 123 business actors. The sample was determined by purposive random sampling using the Slovin formula and obtained as many as 55 people. Data collection techniques through distributing questionnaires and documentation. The data analysis technique uses multiple linear regression analysis. The research results show the influence of competitive strategy and e-commerce on business success. Conclusion: Partial and simultaneous competitive strategy and e-commerce have a positive and significant effect on the success of MSME businesses in Medan Selayang District.